Effect of Glass Fiber Reinforcement on the Mechanical Properties of Polyester Composites - I. R. Antipas (Advanced Engineering Research, 2023)
Introduction. Glass fibers significantly improve the quality of composite materials, make them lighter, stronger, more corrosion resistant and thermally stable. Strengths and weaknesses of specific composites are actively discussed in the scientific and applied literature. At the same time, the effect of the ratio of fibers and matrix material on the mechanical characteristics of composites has not been sufficiently investigated. The presented study is intended to fill this gap. The work is aimed at manufacturing a composite material on a polymer basis reinforced with glass fiber, and investigating the influence of weight ratios of elements on the mechanical characteristics of the composite. For the first time, a report on the comparison of the characteristics of composites (with different fiber content) to each other and to steel is published.Materials and Methods. Fiberglass and polyester were used as starting materials with the addition of a mediator to speed up the molding process. The samples were made manually and tested for tensile strength, hardness, and impact strength using standard equipment. The results were summarized in the form of tables, visualized in the form of graphs, and processed by comparative analysis.Results. The technique of creating samples and methods of their testing were described. The research showed that hardness, tensile strength and impact resistance increased with a growth in the percentage of randomly distributed fiberglass to 50% with 50% unsaturated polyester. In this case, the maximum values of tensile strength — 175.4 MPa, hardness — 38 HV and impact resistance — 1.56 J/mm2 were obtained. The inexpediency of exceeding the proportion of fiberglass by more than 50% was experimentally proven, since mechanical properties deteriorated. This was due, in particular, to the fragility of the glass, which, if the proportions were violated, was transmitted to the entire composite. In addition, with an excessively high volume of reinforcing fibers, the resin was not enough for high-quality bonding of the elements, which significantly reduced the strength of the material. Most of the mechanical characteristics of a composite made of 50% polyester and 50% fiberglass are better than those of steel.Discussion and Conclusion. It has been proved that the properties of the composite material depend significantly on the glass fiber content. The resulting composite was compared to steel. It turned out that it had better mechanical characteristics and less weight. This allows us to recommend the material for boat hulls.